Concept mapping a potential pedagogical strategy to foster meaningful learning in physiology students - Smita R. Sorte; Suvarna Sande; Sachin B. Rathod; Vinu A. Vij; Jyotsna Gumashta; Gayatri Muthiyan; Ashwini Patil (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Understanding of human physiology is critical for clinical practice and disease management. Escalating the teaching-learning method to improve conceptual knowledge may help the students to apply their knowledge in clinical scenarios. The present study was conducted to teach the use of concept mapping as a learning strategy to foster meaningful learning in physiology, compare its impact as a learning tool with traditional methods on meaningful learning, assess the cognitive gain, and find student's perception regarding concept mapping. MATERIALS AND METHODS: The interventional study was conducted on first-year MBBS students. Depending upon marks obtained in previous internal assessments, the students were classified into "rapid learners" (RL) and "potential learners" (PL). By simple random sampling technique, both groups were divided into interventional (concept mapping) and control groups (question-answer discussion). After a pretest, all students had a lecture on glomerular filtration. The assignment was given to the interventional group to prepare a concept map on glomerular filtration, and question-answer were discussed for control groups. A surprise posttest was conducted after 2-3 days. RESULT: In our study, all four groups showed significant differences in the pretest and posttest scores using a paired t-test (P < 0.05). The mean score of gain in learning, raw gain (G0), absolute learning gain, relative learning gain, and average normalized gain compared between the interventional group and controls group showed statistically significant performance improvement in both RL and PL groups. CONCLUSION: The concept mapping strategy was more efficacious than the question-answer discussion. Concept mapping is an impactful learning tool to improve cognitive gain and potential pedagogical strategy to foster meaningful learning in physiology students.